Evidence-Based Decision Making in Dentistry Multidisciplinary Management of the Natural Dentition - Rosen, Eyal.; Nemcovsky, Carlos E.; Tsesis, Igor.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This clinically oriented book covers all aspects of the evidence-based decision making process in multidisciplinary management of the natural dentition. The book opens by clarifying the principles of evidence-based decision making and explaining how these principles should be applied in daily practice. Individual chapters then focus specifically, and in detail, on endodontic, periodontal, and prosthetic considerations, identifying aspects that need to be integrated into decision making and treatment planning. Evidence-based decision making with regard to preservation of the natural tooth versus extraction and implant placement is then discussed, and a concluding chapter examines likely future trends in dentistry and how they may affect clinical decision making. The authors include leading endodontists, periodontists, and prosthodontists. Given the multidisciplinary and comprehensive nature of the book, it will be relevant and interesting to the entire dental community.
Introduction to evidence-based decision making in the multidisciplinary management of the natural dentition -- Principles of evidence-based decision making -- Evidence-based decision making in dentistry: the endodontic perspective -- Evidence-based decision making in periodontal tooth prognosis and maintenance of the natural dentition -- Evidence based decision making in restoration of the natural dentition -- Preserving The Natural Tooth Versus Extraction And Implant Placement- An Evidence Based Approach -- Case selection for the use of Cone Beam Computed Tomography in dentistry based on diagnostic efficacy and risk assessment -- Evolving new strategies for Periodontal, Endodontic and Alveolar Bone Regeneration.
Keywords: Dentistry; Dentistry; Dentistry